DEVELOPMENT OF REDUCTION REACTION LEARNING USING COMPUTER BASED LEARNING METHOD - Heri Sunandar; Soni Bahagia Sinaga (Sean Institute, 2020)
Chemistry is the study of objects, their characteristics, structure, composition, and changes caused by interactions with other objects or chemical reactions. Chemistry is often referred to as the